Contextualization of Progressive Law in Designing Hybrid Legal Counseling Methods as an Effort to Build Public Legal Awareness - Serah, Yenny Aman; Purwanto, Purwanto; Febrianawati, Febrianawati; Mutiara Sirait, Resmaya Agnesia; Astono, Agustinus (UNISSULA, 2024)
Conservatism, combined with a positivist view of the law, causes the law to become rigid and merely an artificial construct. Legal actors, who should be reformist agents of change, now focus solely on rules. The implications of this static application of the law by legal actors, particularly in relation to legal counselling methods, hinder legal counselling programs aimed at building public legal awareness. Based on this, it is necessary to find a legal counselling method that is more relevant to current times—one that aligns with public aspirations, is creative, innovative, and can be effectively implemented in the community. The problem formulation in this study is how to contextualize progressive law in designing a hybrid legal counselling method as an effort to build public legal awareness. The purpose of this study is to explore and contextualize progressive law in designing such a method. This study employs an empirical legal research method with a sociological-juridical approach. The research was conducted in West Kalimantan Province, focusing on Bengkayang Regency and Landak Regency. The conclusions of this study were drawn deductively. This study concludes that the contextualization of progressive law within the hybrid legal counselling method in West Kalimantan must be based on legal awareness and the needs of the community. This method aims to liberate society from conservative rules. Additionally, the effectiveness of this method is highly dependent on the ability of legal counsellors to continuously innovate and progress while upholding legal ethics.